Performance and emissions of light-duty diesel vehicle fuelled with non-surfactant low grade diesel emulsion compared with a high grade diesel in Malaysia. (15th December 2016) - Ramlan, Nur Atiqah; Yahya, Wira Jazair; Ithnin, Ahmad Muhsin; Hasannuddin, A.K.; Norazni, Siti Amiliyana; Mazlan, Nurul Aiyshah; Sugeng, Dhani Avianto; Bahar, Nadia Dayana; Koga, Tsuyoshi
Highlights: Fuel consumption of non-surfactant W/D emulsion reduced to 7.39% compared to ULSD. NOx of non-surfactant W/D emulsion was lower than low grade diesel, but higher than ULSD. CO for non-surfactant W/D emulsion was higher than both diesels. Non-surfactant W/D emulsion fuel was proven applicable. Abstract: The use of water-in-diesel (W/D) emulsion as a diesel substitute has imposed significant interest due to its benefits to engine performance and exhaust emissions. However, the development on emulsification technology especially without using surfactant is still not widely known. Therefore, in this study, a study into the application of non-surfactant W/D emulsion has been done with the objective to analyze the potential of non-surfactant W/D emulsion made from low grade diesel as a substitute for higher grade diesel. This study was conducted using light-duty diesel vehicle, a 1 ton truck tested in a chassis dynamometer. A variety of test fuels was used, comprises of Diesel Euro 5 (DE5), Diesel Euro 2 (DE2) and emulsion made from Diesel Euro 2 (EDE2). EDE2 was produced real time just before it is injected into the diesel engine, with water percentage of 6.5% and no additional surfactant. The testing was executed on a chassis dynamometer in accordance to the West Virginia (WVU) 5 Peak-Cycle standard. Among the data collected are fuel consumption, exhaust temperature, gas emissions (NOx, CO and CO2 ) and smoke number. The results show that the EDE2 improved the engine fuel consumption by 7.39% compared to DE5. As for exhaust emissions, EDE2 produced slightly higher NOx and CO compared to DE5. However, CO2 and smoke of EDE2 were found to be lower. For that reason, with some adjustments, non-surfactant W/D emulsion fuel made from low grade diesel has a potential to be applied in road transport with some adjustment in order to replace the high grade diesel.